Measuring the Impact of Economic and Environmental Drivers on Human Development: A Comparison between Developed and Less Developed Countries - Hashmat, Afsheen; Ghouse, Ghulam; Ahmad, Nawaz (Pakistan Journal of Humanities and Social Sciences, 2024)
The world faces a variety of environmental problems that have a significant impact on human development. In light of this, this study examines how environmental degradation affects human development while accounting for factors such as gender, income, and educational disparities, unemployment, GDPPC, institutional quality, and urbanization. The comparison between developed and developing nations is done between 1996 and 2021. Using both ecological footprints and carbon dioxide (CO2) emissions figures to measure the environmental impact on developed and less developed countries provides a more comprehensive approach to checking the environmental damage’s impact on human development. Overall, the generalized moment’s analysis method approves robust relationships between the study variables. The GMM analysis mentioned that environmental quality affects human development in the selected countries by increasing the ecological footprint and carbon emissions. Likewise, inequality in income, education, and gender has a huge negative impact on human development, as unemployment also has the opposite effect on human development in the case of less developed countries instead of developed countries. On the other hand, it has been proven that GDP, quality of institutions and urbanization confirm human welfare. Therefore, taking into account these main findings, some broad policies are required to contribute to enhancing human welfare.